CURRENT ISSUES IN ENSURING THE LIQUIDITY OF NON-BANK CREDIT INSTITUTIONS (World Economics and Finance Bulletin, 2026)
Non-bank credit institutions (NBIs) play a vital role in the financial system, providing access to financial services (microloans, transfers) for individuals and businesses that are unavailable through banks. They specialize in fast, highly specialized transactions, such as account-free transfers, cash collection, and pawnshop lending. The stability of NBIs, in turn, depends directly on their liquidity, as sufficient liquidity is a prerequisite for their solvency.